Growth of Cutibacterium acnes is common on osteosynthesis material of the shoulder in patients without signs of infection. (3rd September 2018) - Both, Anna; Klatte, Till O; Lübke, Andreas; Büttner, Henning; Hartel, Maximilian J; Grossterlinden, Lars G; Rohde, Holger
Abstract : Background and purpose — Cutibacterium acnes, formerly known as Propionibacterium acnes, is often isolated from deep tissues of the shoulder. It is recognized as an important causative agent of foreign-material associated infections. However, the incidence and significance of its detection in tissues from patients without clinical evidence for infection is unclear. We assessed the incidence of C. acnes colonization of osteosynthesis material in asymptomatic patients, and evaluated the short-term outcome in relation to the microbiological findings. Patients and methods — We microbiologically analyzed osteosynthesis material of 34 asymptomatic patients after surgery on the clavicle. Material obtained from 19 asymptomatic patients after osteosynthesis of the fibula served as a control group. Patients were clinically followed up for 3–24 months after removal of the osteosynthesis material. Results — Bacteria were recovered from devices in 29 of 34 patients from the clavicle group. 27 of 29 positive samples grew C. acnes . Isolation of C. acnes was more common in male than in female patients. No bacterial growth was observed on foreign material from patients in the fibula group. All patients remained asymptomatic at follow-up. Interpretation — Growth of C. acnes is common on osteosynthesis material of the shoulder, especially in males. Samples were positive irrespective of clinical signs of infection. Therefore, detection of C. acnes in this clinical setting is of questionable clinical significance. The high positivity rate in asymptomatic patients discourages routine sampling of material in cases without clinical evidence for infection.